PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Christi, Verina; Munari, Munari (E-Jurnal Manajemen, 2021)
The objective of this study is to determine the effect of financial ratios on stock prices in cigarette companies listed in Bursa Efek Indonesia (Indonesia Stock Exchange) during the first quarter of 2017 until the last quarter of 2019, either partially or simultaneously. The financial ratio being examined in this study include quick ratio (QR), net profit margin (NPM), total asset turnover (TATO), and debt to asset ratio (DAR). The population of this study was the cigarette companies listed in Indonesia Stock Exchange in the first quarter of 2017 until the last quarter of 2019. The research sample was 4 cigarette companies obtained by purposive sampling technique. The data collection techniques that used were documentation and literature study. Data analysis was performed using multiple linear regression analysis techniques. The results of this study showed that partially QR, NPM, and DAR variables have a significant effect on stock prices, while TATO has no effect on stock prices. Simultaneously the QR, NPM, TATO, and DAR variables affect the stock prices. Keywords i: Harga Saham; QR; NPM; TATO; DAR